وظيفة البنى اللغوية في تشكيل رؤية الشاعر أدونيس للعالم – ديوان الحصار – نموذجاً - Ubaid Asy-Syabiel, Abir (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2018)
The Function of Linguistic Structures in Shaping Adonis's Vision of the World: The Siege as an Applied Model We chose the poet Adonis for a reason: he is a problematic poet, critic and thinker, who came out of the